Semisynthetic derivatives of massarilactone D with cytotoxic and nematicidal activities - Teponno, Rémy B.; Noumeur, Sara R.; Stadler, Marc (Beilstein Journal of Organic Chemistry, 2025)
Massarilactones constitute a rare class of polyketides produced mainly by endophytic fungi. Given that semisynthetic derivatives often exhibit biological activities greater than those of the substrates, seven previously unreported derivatives of massarilactone D, compounds 2–8, were synthetized by acylation with methacryloyl chloride, cinnamoyl chloride, 4-bromobenzoyl chloride, trans-2-methyl-2-butenoyl chloride, and crotonyl chloride. These compounds were evaluated for their cytotoxic activity against the murine fibroblasts L929, human cervix carcinoma KB-3-1, human lung carcinoma A549, human prostate cancer PC-3, epidermoid carcinoma A431, ovarian carcinoma SKOV-3, and breast cancer MCF-7 cell lines. Compounds 2 and 3 exhibited significant cytotoxicity against all the tested cells. Some of the semisynthetic derivatives were also tested for their nematicidal activity and compound 4 displayed signiﬁcant and selective nematicidal activity with LD90 and LD50 of 100 and 12.5 µg/mL, respectively. Since the parent compound was not active, the present study supports the fact that the acylation reaction can improve bioactivities of some natural products.
Keywords: acylation reaction; cytotoxic activity; massarilactone D; nematicidal activity